OSCEai dermatology: Augmenting dermatologic medical education with Large Language Model GPT-4 - Park, Ye-Jean; Guo, Eddie; Sachdeva, Muskaan; Ma, Bryan; Mirali, Sara; Rankin, Brian; Nathanielsz, Nikki; Abduelmula, Abrahim; Lapa, Tatiana; Gupta, Mehul; Champagne, Trevor (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2025)
Implication StatementOSCEai Dermatology demonstrates how large language models (LLMs) like GPT-4 can be integrated into medical education to enhance trainees’ history taking and management skills in an OSCE-like format, including in visual-based specialties like dermatology. By generating diverse, realistic skin cancer role-play scenarios across different skin tones alongside the integration of pre-existing, evidence-based images, the app provides learners with valuable, personalized feedback. This innovation offers a novel, interactive learning tool that supplements traditional teaching methods and can be applied across various specialties. Institutions can adopt or adapt similar LLM-driven educational tools to introduce trainees to a wider range of clinical cases, fostering improved diagnostic skills and patient-centred, culturally sensitive care.